GAP ANALYSIS IN DELI WATERSHED MANAGEMENT MEASURED BY STAKEHOLDERS’ SOCIAL FACTORS DELI NORTH SUMATERA - Jen Christ David; Abdul Rauf; Hamdani Harahap (Universitas Negeri Medan, 2022)
A watershed is an area encompassing rivers and tributaries, which functions as a container, a reservoir, a water drainage system, and a home for human activities and other living things, either living on the banks of the river or living in a watershed. This research is a qualitative descriptive study that used interviews and questionnaires to collect the data. This study examined four main factors in Deli Watershed Management: stakeholders' capacity level, knowledge levels, attitudes, and the gap in watershed management. The t-test result showed the correlation's capacity level as an insignificant variable (p> 0.05). The regression model that describes the correlation between stakeholders' knowledge level, stakeholders' attitudes, simultaneously, and the gap in the management of the Deli Watershed Management amounting to y = 1.164 - 0.173 x1 - 0.470x2 where x1 = level of knowledge and x2 = attitudes. The value of r = 0.704 indicates that the correlations between these variables are strong. Meanwhile, the adjusted R square value is 0.460. The F-test suggests that 46% of the variation in the gap in the Deli Watershed Management was due to stakeholders' knowledge levels and attitudes in implementing the management. Thus, social inequality in watershed management correlates with stakeholders' knowledge and perspectives. Still, it does not have an accurate correlation with stakeholders' attitudes.Keywords: Watershed, Deli, Management, Gap Analysis, Correlation